PLGA-PEG Nanoparticles Loaded with Cdc42 Inhibitor for Colorectal Cancer Targeted Therapy - Sanazar Kadyr; Altyn Zhuraliyeva; Aislu Yermekova; Aigerim Makhambetova; Daulet B. Kaldybekov; Ellina A. Mun; Denis Bulanin; Sholpan N. Askarova; Bauyrzhan A. Umbayev (MDPI AG, 2024)
Background/Objectives: An inhibitor of small Rho GTPase Cdc42, CASIN, has been shown to reduce cancer cell proliferation, migration, and invasion, yet it has several limitations, including rapid drug elimination and low bioavailability, which prevents its systemic administration. In this study, we designed and characterized a nanoparticle-based delivery system for CASIN encapsulated within poly(lactide-co-glycolide)-block-poly(ethylene glycol)-carboxylic acid endcap nanoparticles (PLGA-PEG-COOH NPs) for targeted inhibition of Cdc42 activity in colon cancer. Methods: We applied DLS, TEM, and UV-vis spectroscopy methods to characterize the size, polydispersity index, zeta potential, encapsulation efficiency, loading capacity, and in vitro drug release of the synthesized nanoparticles. The CCK-8 cell viability test was used to study colorectal cancer cell growth in vitro. Results: We showed that CASIN-PLGA-PEG-COOH NPs were smooth, spherical, and had a particle size of 86 ± 1 nm, with an encapsulation efficiency of 66 ± 5% and a drug-loading capacity of 5 ± 1%. CASIN was gradually released from NPs, reaching its peak after 24 h, and could effectively inhibit the proliferation of HT-29 (IC50 = 19.55 µM), SW620 (IC50 = 9.33 µM), and HCT116 (IC50 = 10.45 µM) cells in concentrations ranging between 0.025-0.375 mg/mL. CASIN-PLGA-PEG-COOH NPs demonstrated low hemolytic activity with a hemolytic ratio of less than 1% for all tested concentrations. Conclusion: CASIN-PLGA-PEG-COOH NPs have high encapsulation efficiency, sustained drug release, good hemocompatibility, and antitumor activity in vitro. Our results suggest that PLGA-PEG-COOH nanoparticles loaded with CASIN show potential as a targeted treatment for colorectal cancer and could be recommended for further in vivo evaluation.